GRADIENT ESTIMATES FOR POSITIVE SMOOTH f-HARMONIC FUNCTIONS - 陈立 陈文艺 (Acta mathematica scientia, 2010)
For Riemannian manifolds with a measure, we study the gradient estimates for positive smooth f-harmonic functions when the ∞-Bakry-Emery Ricci tensor and Ricci tensor are bounded from below, generalizing the classical ones of Yau （i.e., when ： is constant）.